Managing Country Risk in an Age of Globalization A Practical Guide to Overcoming Challenges in a Complex World - Bouchet, Michel Henry (Springer International Publishing, 2018)
This book provides an up-to-date guide to managing Country Risk. It tackles its various and interlinked dimensions including sovereign risk, socio-political risk, and macroeconomic risk for foreign investors, creditors, and domestic residents. It shows how they are accentuated in the global economy together with new risks such as terrorism, systemic risk, environmental risk, and the rising trend of global volatility and contagion. The book also assesses the limited usefulness of traditional yardsticks of Country Risk, such as ratings and rankings, which at best reflect the market consensus without predictive value and at worst amplify risk aversion and generate crisis contamination. This book goes further than comparing a wide range of risk management methods in that it provides operational and forward-looking warning signs of Country Risk. The combination of the authors' academic and market-based backgrounds makes the book a useful tool for scholars, analysts, and practitioners. .